A Cross-national Study of Environmental Performance and Culture: Implications of the Findings and Strategies. Issue 4 (August 2019) - Kumar, Sushant; Giridhar, Vishlavath; Sadarangani, Pradip
Abstract: The study investigates the impact of culture on environmental performance across 78 countries. The article explores the possible relationship with two datasets of international indices: (a) the six dimensional index of national culture proposed by Hofstede and (b) the environmental performance index (EPI) published by Yale Center for Environmental Law and Policy. It is widely established that population and economic development of a country play significant role in the improvement of environmental performance. In our study, we examine the impact of population growth rate and per-capita gross domestic product (GDP) on environmental performance using structure equation modelling. The results show that environmental performance is significantly influenced by the culture of the country. Per-capita GDP and population growth rate have a positive and negative relationships on the environmental performance. By measuring the cultural dimensions and their impact on global environmental performance, countries could identify the favouring cultural dimensions and design appropriate strategy to optimize the environmental performance. The article proposes the practical implication of results and strategies to improve environmental performance. The study is among the first in studying the cultural dynamics on environment and identify its favourable and adverse relationships for an optimum strategy.